Improving Thermal Comfort and Energy Efficiency in Chilean Patagonian Homes with Thermal Storage-Enhanced Radiant Floors with Phase Change Materials - Venegas-Troncoso, T (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Phase Change Materials (PCMs) have been commonly used to enhance the thermal storage capacity of building envelopes. Their use aims to improve indoor temperatures and reduce space-conditioning energy use. This study proposes a methodology to analyze the behavior of PCMs based on studying detailed variables such as PCM state, heat flux, and temperature, in addition to sought-after macroscopic variables such as room temperature and yearly energy use. This supplementary use of detailed variables helps to fully understand the behavior of the PCMs and detect undesirable operation conditions that cannot be observed from the macroscopic variables only; the detailed variables may alter the selection of a PCM for thermal envelope enhancement. This methodology was deployed to analyze a particular case. PCMs were integrated into the structure of a radiant heating floor element of a wooden house located in Coyhaique, Chilean Patagonia. The house was modeled using DesignBuilder v6.1.5.002 and the results were validated with onsite measurements. Twenty-three organic PCMs with melting temperatures ranging from 11 °C to 44 °C and varying thickness were considered. Three PCMs showed melting–solidification cycles at the operational temperatures. The detailed analysis of the PCM layer state, heat flux, and temperatures were performed using EnergyPlus v9.5.0. The most significant heating energy reduction was observed with a melting temperature of 42 °C, reaching up to 2.8%, and the maximum reduction in thermal discomfort hours was 27% for the 44 °C melting-temperature PCM. The integrated heat flux and PCM state analysis to determine the working conditions of the PCM allowed for the detection of certain combinations of materials and thicknesses that showed that, albeit presenting favorable macroscopic variables, the PCM was not behaving as expected, and therefore, the material was misused. The results show that the careful selection of PCM to enhance the thermal inertia of heated floors can yield energy savings and thermal comfort improvements, but its selection requires careful analysis well beyond the macroscopic variables. © 2025 by the authors.